Magnetostriction of martensite - James, R. D.; Wuttig, Manfred (Philosophical magazine. A, Physics of condensed matter. Defects and mechanical properties, 1998)
A general strategy is described for inducing magnetostriction in ferromagnetic martensitic materials. An analysis of domain redistribution caused by a magnetic field is given, and certain relations between material constants that promote this effect are described. These relations suggest a 'constrained theory of magnetostriction' which is used to predict strain against field in a tetragonal martensite subject to an orthogonal biaxial magnetic field and uniaxial stress. These predictions are compared with the corresponding experiments in Fe 70 Pd 30 . Reversible field-induced strains of 0.6% are exhibited in this system. Microstructural observations confirm that these strains are caused by a field-induced redistribution of martensitic twins.